Effects of sodium arsenate and arsenite on male reproductive functions in Wistar rats. Issue 6 (18th March 2016) - Souza, Ana Cláudia Ferreira; Marchesi, Sarah Cozzer; Ferraz, Rafael Penha; Lima, Graziela Domingues de Almeida; Oliveira, Juraci Alves de; Machado-Neves, Mariana
ABSTRACT: Arsenic (As), in the form of trivalent arsenite or pentavalent arsenate, is a ubiquitous toxic compound naturally occurring in the environment. This study aimed to evaluate the impact of two different forms of inorganic As on reproductive parameters following oral exposure. Adult Wistar male rats were exposed to sodium arsenite or arsenate at concentrations of 0.01 mg/L or 10 mg/L for 56 d in drinking water. Sodium arsenite at both concentrations and sodium arsenate at 10 mg/L produced reduction in daily sperm production, in number of spermatids in the testis, and in sperm in the epididymal caput/corpus regions. Changes in epididymal morphometry were variable and region specific. Total and progressive sperm motility and sperm morphology did not differ markedly between controls and animals exposed to As. The body and reproductive organs weights, as well as testosterone concentration, remained unchanged among all groups. In conclusion, As exposure in drinking water over 56 d produced damage in male reproductive functions in adult rats, suggesting that fertility problems might occur. Therefore, additional studies need to be undertaken to investigate potential mechanisms underlying sodium arsenite- and arsenate-induced disturbances in fertility and reproductive performance.